Implementation Of Data Mining For Determining Majors Using K-Means Algorithm In Students Of SMA Negeri 1 Pangkalan Kerinci - Yuda Irawan (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2019)
SMA Negeri 1 Pangkalan kerinci is one of the middle schools located at Jalan Lintas Timur Kerinci Pelalawan Indonesia which currently has 2 majors namely Science and IPS. This student majors can lead learners to focus more on developing their own abilities and interests. Selection of inappropriate majors can be very detrimental to students of their interests and careers in the future. With the majors are expected to maximize the potential, talent or individual talents, so as to maximize academic value. Based on the background, then by applying data mining techniques are expected to help students to determine the correct majors in accordance with the criteria set. Data mining techniques used in the determination of this department using K-Means Algorithm.